Ovarian Cyst Disease in Cattle: Bioanalysis of Associated Hormones - Ammar M.K. AL-azzawi; Ali Abbas Ali; Ghassan H. Jameel (Institute of Medico-legal Publications Pvt Ltd, 2022)
Ovarian cysts are structures that appear on ovaries, their size reaches 2.5 cm in diameter or greater remainingfor 10 days or more if they are untreated. They are classified into three major categories includes follicularcysts, luteinized follicular cysts, and cystic corpora luteal result in failure of reproduction in dairy cows. Thereisasignificant depression in the mean values of FSH and LH in the repeat breeder cows (infected group) whencompared with the normal cows (control group). There is a significant elevation in the mean values of theprolactin hormone in the repeat breeder cows. In recommendation, balanced feeding to dairy cows with highmilk production would decrease the risk factors associated with cystic ovary syndrome.